TAMPILAN REPRODUKSI HASIL INSEMINASI BUATAN MENGGUNAKAN SEMEN BEKU HASIL SEXING PADA SAPI PERSILANGAN ONGOLE DI PETERNAKAN RAKYAT - Lieyo Wahyudi; Trinil Susilawati; Nurul Isnaini (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2014)
The purpose of this research was to determine the success of AI using sexed semen results based on NRR, S/C, CR, and rectal palpation were also determine. The total number of 81 acceptors divided into 3 treatment groups, such as P0 (non- sexed semen) ; P1 (Frozen semen Sexed using White Yolk Sedimentation), P2 (Frozen semen sexed using Percoll Gradient Centrifugation) . The results showed the NRR percentage of P0, P1 and P2 were between the treatments are P0 of 74.07 ± 12:00%; 65.43 ± 5.66% and 64.19 ± 8:56% respectively. Furthermore the highest of CR was in P0 44%, P2 25.91% and P1 18.51%. Conclution of this research was the highest percentage of pregnancy was 59.25 %(P0) , P1 51.85% and the lowest was in 44.44%. The S/C was in (P0) 2.31 follow by 3.00 in P2 and 3.33 in P1. Key words : artificial insemination , frozen semen sexed, the percentage of Gestation and feed